Focal nodular hyperplasia‐like lesion of the liver with focal adenoma features associated with idiopathic portal hypertension. Issue 10 (8th January 2014) - Sugimoto, Katsutoshi; Kondo, Fukuo; Furuichi, Yoshihiro; Oshiro, Hisashi; Nagao, Toshitaka; Saito, Kazuhiro; Yoshida, Hiroshi; Imai, Yasuharu; Fukusato, Toshio; Moriyasu, Fuminori
<x xml:space="preserve">Abstract</x> Great progress has been made in the diagnosis of focal nodular hyperplasia (FNH) and hepatocellular adenoma (HCA) in the last few years due to the use of molecular criteria. This has allowed us to identify a new type of hepatic nodule. In this case report, we present a male patient with a hepatic nodule associated with idiopathic portal hypertension (IPH) pathologically exhibiting not only the morphological features of FNH, such as ductular reactions, dilated sinusoids, major vascular abnormalities and an immunohistochemical "map‐like" pattern of glutamine synthetase (GS), but also the immunohistological features of focal HCA, such as strong expression of serum amyloid A and C‐reactive protein and weak expression of GS. As the final diagnosis, the nodule was identified as an FNH‐like lesion with focal inflammatory hepatocellular adenoma.